Type 2 diabetes microenvironment promotes the development of Parkinson’s disease by activating microglial cell inflammation - Zhang, Bohan; Song, Chengyuan; Tang, Xiao; Tian, Min; Liu, Yuqian; Yan, Zhuoran; Duan, Ruonan; Liu, Yiming (Frontiers in Cell and Developmental Biology, 2024)
Objective Parkinson's disease(PD) is the second most common neurodegenerative disease in the world, and type 2 diabetes(T2DM) and PD are influenced by common genetic and environmental factors. Mitochondrial dysfunction and inflammation are common pathogenic mechanisms of both diseases. However, the close association between PD and T2DM and the specific relationship between them are not yet clear. This study aimed to reveal the specific connection between the two diseases by establishing a mouse model of comorbid PD and T2DM, as well as a Bv2 cell model. Methods: C57BL/6 mouse were used to construct a model of PD with T2DM using streptozotocin and rotenone, while Bv2 cells were used to simulate the microenvironment of PD and T2DM using rotenone and palmitate. Behavioral tests were conducted to assess any differences in motor and cognitive functions in mouse. Immunohistochemistry was used to analyze the number of dopaminergic neurons in the substantia nigra region of mouse. Western blotting was used to detect the expression levels of TH, P-NFκB, NFκB, Cyclic GMP-AMP synthase (cGAS), and Stimulator of interferon genes (STING) proteins in the substantia nigra region of mouse and Bv2 cells. qRT-PCR was used to analyze the expression levels of IL1β, IL6, and TNF-α. Seahorse technology was used to assess mitochondrial function in Bv2 cells. Results: T2DM exacerbated the motor and cognitive symptoms in mouse with PD. This effect may be mediated by disrupting mitochondrial function in microglial cells, leading to damaged mtDNA leakage into the cytoplasm, subsequently activating the cGAS-STING pathway and downstream P-NFκB/NFκB proteins, triggering an inflammatory response in microglial cells. Microglial cells release inflammatory factors such as IL1β, IL6, and TNF-α, exacerbating neuronal damage caused by PD. Conclusion Our study results suggest that T2DM may exacerbate the progression of PD by damaging mitochondrial function, and activating microglial cell inflammation. The detrimental effects on Parkinson's disease may be achieved through the activating of the cGAS-STING protein pathway.